Mapping the Problem Writing Assignment - Kansas State University, K-State First (Kansas State University. K-State First., 2014)
This assignment outlines two essay prompts for "The Ghost Map," including the first set of essay questions, identification of a campus problem, inclusion of a corresponding map and eight photographs. The second set of essay questions requests a corresponding public health campaign and three outside sources.
Keywords: Ghost Map, The; Writing assignment; Common reading program; Application of learning; Mapping; Public health; Papers (document genres)